Core Java. - Horstmann, Cay S., 1959- (Rough cuts., 2022)
The #1 Java Guide for Serious Programmers: Fully Updated through Java 17 Core Java, Volume II: Fundamentals, Twelfth Edition, is the definitive guide to writing robust, maintainable code. Whatever version of Java you are usingup to and including Java 17this book will help you achieve a deep and practical understanding of the language and APIs. With with authoritative coverage of enterprise programming, networking, databases, security, modularization, internationalization, code processing, native methods, and more. Cay S. Horstmann explores sophisticated new features with depth and completeness, demonstrating how to use them to build professional-quality applications This book is written for readers with prior programming experience who are looking for in-depth coverage of the Java language and platform. You'll learn about all language features in detail, including the recent improvements in Java 17. The examples are carefully crafted for easy understanding and maximum practical value, so you can rely on them to jump-start your own code.. For 25 years, Core Java has prepared serious programmers for serious Java programming. Master advanced techniques, idioms, and best practices for writing superior Java code Make the most of enhanced Java I/O APIs, object serialization, and regular expressions Efficiently connect to network services, implement servers and the improved HTTP client, and harvest web data Process code via scripting and compiler APIs, and use annotations to generate code and files Deepen your understanding of the Java Platform Module System, including recent refinements Deepen your understanding of the Java Platform Module System, including recent refinements Preview powerful new APIs for accessing "foreign" functions and memory Core Java, Volume II: Advanced Features, Twelfth Edition is the reliable source for expert coverage of Java 17 enterprise features, the module system, annotations, networking, security, and advanced UI programming.